Serbia and the Serbs in World War Two - Ramet, Sabrina P. author. aut Link
XVII, 324 p.
Keywords: A valuable and objective reassessment of the role of Serbia and Serbs in WWII. Today, Serbian textbooks praise the Chetniks of Draža MIhailovi? and make excuses for the collaboration of Milan Nedi?'s regime with the Axis. However, this new evaluation shows the more complex and controversial nature of the political alliances during the period.